Proceedings of the Third International Afro-European Conference for Industrial Advancement - AECIA 2016 (Advances in Intelligent Systems and Computing,, 2018)
The Afro-European Conference for Industrial Advancement (AECIA) brought together the foremost experts and excellent young researchers from Africa, Europe and the rest of the world to disseminate the latest results from various fields of engineering, information and communication technologies. This volume gathers the carefully selected papers from the third installment of the AECIA, which was held in Marrakech, Morocco from November 21 to 23, 2016. The papers address important topics like Automation Systems, Intelligent Techniques and Algorithms, Information and Communication Technology (ICT) Applications in Engineering, Control, Optimization and Processing, as well as manufacturing-related topics. As such, it offers a valuable reference guide for researchers, students and practitioners in the fields of computer science and engineering.